Professors’ academic reasoning behind the use and non-use of educational technology tools for class development in the Intensive English and French subjects of the Bachelor in Modern Languages with Specialization in French and English, of the Department of Foreign Languages of the School of Arts and Sciences of the University of El Salvador, Semester I-2018 - Duque Rodríguez, Marcela María; López Hernández, Wendy del Carmen; Martínez Meléndez, Lisseth Carolina (2024)
The use of Educational Technology tools (ET tools) in the process of teaching and learning a foreign language has become so important at the Foreign Language Department (FLD), though there are still some professors who prefer to teach in a traditional way without using any type of technological equipment in classes. This present research work was focused on finding out the academic reasoning behind the implementation and non-implementation of these technological devices and the uses that professors of the FLD give to these ET tools during classes as well as the way they help students to develop the linguistic macro skills. To have a whole overview of the object of study of this research, a class observation phase was carried out in the selected class groups, professors in charge of the selected classes were interviewed, and students were asked to answer an auto-administered questionnaire. The results revealed when and how professors made use or non-use of these technological devices and their opinions and reasons of using them or not; besides that, students’ points of view disclosed how the use or non-use of ET tools in classes impacts their English learning. Reflections and recommendations have been made based on the obtained results to consider implementing the use of ET tools more in the Foreign Language Department of the University of El Salvador.